Relationship between Occupational Safety and Health (OSH) and Work Accidents among Fire and Rescue Officers in Pekanbaru City - Suri, Anggun; Susanti, Nurvi; Makomulamin, Makomulamin (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Occupational Safety and Health (OSH) is essential for creating asafe,comfortable, andhealthy work environment. Its main goal is to prevent workplace accidents and occupational diseases that can endanger lives and reduce productivity. This study examines the relationship between OSH and workplace accidents among firefighters in Pekanbaru City from 2022 to 2024. Using an observational method with a quantitative analytic approach and a cross-sectional design, 163 respondents participated. Data analysis included univariate and bivariate techniques. The results show significant relationships between workplace accidents and OSH knowledge (p=0.014), OSH training (p=0.013), availability of Personal Protective Equipment (PPE) (p=0.002), and implementation of Standard Operating Procedures (SOPs) (p=0.011). However, work fatigue showed no significant effect (p=0.531). Based on these findings, it is recommended that institutions enhance OSH training, education, PPE provision, and consistent SOP enforcement to reduce workplace accidents and improve overall safety and health among firefighters.